A Cognitive-Affective Approach to Foregrounding Categorical-Thematic Patterns in Popular Cinema. Issue 3 (1st December 2021) - Stopel, Bartosz
Abstract: The article sets out to discuss disruptions of the embodied flow of movie perception triggered by foregrounded categorical-thematic patterns. First, categorical-thematic patterns are framed in a cognitive perspective and tied to categorical (or parallel) information processing as opposed schematic (sequential). I argue that the former are not prototypical of embodied movie perception and tend to be disruptive if foregrounded, as they are more prevalent in art cinema. Next, I indicate how categorical-thematic patterns may encourage a type of non-habitual pattern recognition producing a number of emotional and aesthetic effects: delight at pattern isolation, wonder emotions, emotional focus of a story theme, and intensification or modulation of global and empathetic emotions. Finally, I turn to illustrate these points using Pan's Labyrinth, a film that systematically foregrounds categorical-thematic patterns yet naturalizes them, alleviating disruption of movie perception. This, I believe, marks an effective strategy of importing avant-garde film techniques into popular cinema.